Achieving the Quality of Education through the Application of Eight National Education Standards using School-Based Management - Sumaryanti Sumaryanti; Nurtanio Agus Purwanto (STAI Hubbulwathan Duri, 2023)
This study aims to identify and describe the achievement of 8 national education standards in one Madrasah Aliyah in Tebo, Jambi Province, through the application of school-based management (MBS) to improve school quality. This type of research is qualitative with a descriptive approach . The research subjects are school principals and education staff. Data collection techniques are observation, interviews, and documentation. The analytical induction technique used to analyze the data is to develop a theory. Data analysis was carried out using the Miles and Huberman models: data condensation, data display and conclusion drawing. The results of this study explain that School-Based Management (SBM) implemented by one Madrasah Aliyah in Tebo as a school quality management system is able to improve school quality with management that involves the participation of all school components and focuses on programs to improve the quality of graduate students and educators. The achievement of a well-executed SBM management is evidenced by the fulfilment of 8 national education standards. The achievement of 8 national education standards shows a quality improvement in one of the Aliyah madrasas in Tebo with accreditation for five years